A Spatiotemporal Approach in Detecting and Analyzing Hydro-climatic Change in Northwest Algeria - Bouraoui, S.; Medjerab, A. (Engineering, Technology & Applied Science Research, 2022)
Understanding climatic behavior, particularly that of semi-arid regions, is essential in order to optimize water resources management and provide protection from climatic risks. Water resources have great socio-economic and environmental importance. This paper focuses on the statistical analysis of the rainfall regime of northwest Algeria and estimates its spatial distribution and temporal variation. To this end, time series and principal component analysis were performed on rainfall series recorded from 1913 to 2009, representing the annual precipitation from thirty meteorological stations to discover patterns and trends in the studied region. Furthermore, the applied spectral analysis of the time series reveals the existence of a period of approximately 97 years at all stations. ArcGIS along with statistical and analytical tools like SPSS and XLSTAT were utilized in this study of the climatic behavior in northwest Algeria.